Endovascular treatment of central venous stenoses in patients with dialysis shunts - Buriankova, Eva; Kocher, Martin; Bachleda, Petr; Utikal, Petr; Kojecky, Zdenek; Cerna, Marie; Herman, Miroslav (Biomedical papers, 2003)
Objective: Evaluation of long-term results of percutaneous treatment of central vein stenoses or occlusions in patients with haemodialysis shunt.Materials and Methods: In 26 patients with haemodialysis shunts and confirmed central vein stenosis or occlusion, 28 primary percuta-neous transluminal angioplasties (PTA) and 5 repeated PTAs (re-PTA) were performed; in three patients a stent was implanted - primary in one patient and due to early restenosis after PTA in two patients. To maintain stent patency, 10 re-PTA were performed.Results: The technical success rate of primary interventions was 96 % (100 % in stenoses and 50 % in occlusions). Primary post-PTA patency rate was 70 % at 3 months, 60 % at 6 months and 30 % at 12 months.Conclusion: PTA with possible stent implantation is a first-choice method in the treatment of stenoses and occlusions of the central venous system. Despite the relatively frequent re-interventions, endovascular treatment is capable to preserve long-term function of the dialysis shunt. Abbreviations: a-v - arterio-venous; CVS - central venous system; PTA - percutaneous transluminal angioplasty; re-PTA - repeated PTA.
Keywords: Central veins / Stenosis / Occlusion / Endovascular treatment / Angioplasty / Haemodialysis